Optimalisasi Sistem Informasi Inventaris Aset Bumdes Berbasis Web Menggunakan Metode Fast (Framework For The Application Of Systems Thinking) Pada Desa Kemiriombo Kabupaten Wonosobo - Ashatul Ilham Manzis; Khalimaturofi’ah; Luthfi Nur Azizah (CV. ITTC INDONESIA, 2025)
Asset inventory recording at BUMDes Akar Mandiri in Kemiriombo Village is still done manually using books, which is prone to errors and slows down the reporting process. This condition causes delays in decision-making related to repairs or replacements and reduces operational efficiency. This study aims to develop a web-based asset inventory information system using the FAST method to assist in digital asset recording. The Framework for the Application of System Thinking (FAST) method was chosen because it has systematic stages, from scope definition to system installation. The study used a descriptive qualitative method with data collection techniques through observation, interviews, documentation, and questionnaires. The data obtained was used to design a web-based system using PHP, MySQL, HTML, CSS, and Bootstrap. The black box test results showed that all features worked as required, while the user questionnaire results reached 90.3 percent in the excellent category. The implementation of the system proved to be able to address the previous manual recording problems and meet the needs of BUMDes Akar Mandiri. Based on these results, this web-based asset inventory information system was successfully developed and is capable of improving efficiency in asset data collection and reporting. This research is expected to serve as a reference for the development of similar systems in other government institutions.